Fuel-flexible biomass off-gassing: antioxidant potential of agricultural residues for biogenic additives to low-emission wood pellets - Moreira, Bruno Rafael de Almeida [UNESP]; Cruz, Victor Hugo [UNESP]; Junior, Marcelo Rodrigues Barbosa [UNESP]; Lopes, Paulo Renato Matos [UNESP]; da Silva, Rouverson Pereira [UNESP] (Springer Nature, 2024)
Biomass energy is gaining attention as a renewable alternative to fossil fuels due to its potential to mitigate greenhouse gas emissions. However, the storage of fuel-flexible biomass, particularly in environments characterized by fluctuations in temperature and humidity, can lead to the automatic release of pollutants, posing environmental and health concerns. This study aimed to evaluate the antioxidant potential of peanut shells, spent coffee grains, and sugarcane leaves as additives for wood pellets to control off-gassing. Results showcased a sigmoidal nature in the generation of CO2 and degradation of extractives, indicating autogenous deterioration of the pellets. The Gompertz model effectively captured this behavior, enabling accurate estimation of alpha, beta, and k parameters. The control group exhibited an alpha value of 2995.4 mg kg−1, representing the maximum CO2 emissions or extractive degradation without additives. Incorporating peanut shells, spent coffee grains, and sugarcane leaves resulted in reduced alpha values of 2732.1, 2405.2, and 2472.4 mg kg−1, respectively, indicating their capacity to decrease specific CO2 emissions and decelerate extractive degradation. These findings suggest the antioxidant potential of the additives in mitigating CO2 emissions and extractive degradation processes. Enhancing pellet quality, manufacturing processes, and off-gassing control contribute to the viability of biomass energy as an eco-friendly alternative to fossil fuels. Our research contributes to sustainable biomass energy by endorsing biogenic additives as a solution to off-gassing. This holistic approach addresses critical environmental concerns while acknowledging the need for ongoing investigation.
Keywords: Carbon dioxide; Extractives; Peanut shells; Reactive oxygen species; Spent coffee grains; Sugarcane leaves